Impact of different mycorrhizal species and leaf extracts on nutrient content and fruit quality of Satluj Purple plum - Joshi , Thoudam; Amit , Kotiyal; Aditi , Thakur (Plant Science Today, 2025)
Mycorrhizal fungi are mutualistic symbiotic associations among fungi and plants and are a great boon to crop growers. These symbiotic associations enhance the assimilation of nutrients and facilitated the overall plant growth, evaluating how the combination of different mycorrhizal species and leaf extracts influence fruit nutrients and the quality of plums. The recent investigation aimed to assess the impact of different mycorrhizal species combined with leaf extracts on the nutrient content and quality parameters of Satluj Purple plum. The investigation design utilized a Randomized Block Design factorial setup including twelve treatments, which had three replications including a control group. Among the different treatments, Rhizophagus fasciculatus + mixed leaf extracts (custard apple, citrus and guava) @ 0.5 % (RfLE0.5) showed a positive impact on the nutritional content and quality parameters of Satluj Purple plum. The combination of mycorrhizal fungi and leaf extracts was found to be effective in the absorption of nitrogen, phosphorus and potassium, which accounted for better quality and nutrient content. Also, Pearson’s correlation measured the strength and direction of individual treatments and variables, which showed the direct and indirect effects of variables. The study revealed that the application of RfLE0.5 is beneficial not only for mitigating the nutritional content but also for intensifying the calibre of fruit quality of plum fruit.